Individual and region-specific hamstring muscles use during a novel Flywheel Russian belt Deadlift exercise - Pedro Luis Cosio; Lia Moreno-Simonet; Sandra Mechó; Xavier Padulles; Josep Maria Padulles; Joan Aureli Cadefau (Elsevier, 2024)
Background: Despite the implementation of specific exercises to reduce hamstrings strain injuries (HSI) risk, the incidence has remained unchanged over the past 30 years. Therefore, the purpose of the study was to analyze hamstrings muscle activation induced by a novel Flywheel Russian belt Deadlift (FRD) exercise, together with individual muscle-, region- and limb-specific differences. Methods: The activation of hamstring muscles before and immediately after a 10 × 10 FRD training session was assessed by the T2 shift technique through functional magnetic resonance imaging, in one international-level filed hockey male player. The individual use of the biceps femoris long head (BFLH) and short head (BFSH), semitendinosus (ST), and semimembranosus (SM) were analyzed, together with the region-specific activation for each muscle. Results: T2 values significantly increased immediately after exercise in all regions of the hamstring muscles in both dominant and non-dominant lower limb. However, the SM muscle showed a lesser activation, compared to BFLH, BFSH and ST muscles [F(3,106) = 9.557, p < 0.001]. Overall, the most activated muscle by the FRD training session was the biceps femoris (short head +13.8 %, long head, +12.7 %), followed by the ST (+11.3 %), and lastly the SM (+6.9 %). Conclusion: The novel FRD exercise triggers a homogeneous and consistent activation of hamstring muscles. Particularly, the lateral positioning muscles (i.e., BFLH and BFSH) were more activated than the medial positioning muscles (i.e., ST and SM). Therefore, the FRD exercise could enhance training programs to strengthen and activate the hamstring muscles, and specifically, the BFLH, in order to reduce HSI risk.